Influência das precipitações pluviométricas em atributos físico-químicos de frutos da goiabeira 'Paluma' em diferentes estádios de maturação - de Souza, Manoel Euzébio [UNESP]; da Silva, Andréa Carvalho [UNESP]; de Souza, Adilson Pacheco [UNESP]; Tanaka, Adriana Aki [UNESP]; Leonel, Sarita [UNESP] (My University, 2010)
The objective of this work was evaluating the influence of weekly pluviometrics precipitations accumulated in physical and chemical characteristics of fruits of guava tree 'Paluma', in different ripening stadiums. The following attributes were analyzed: fresh weight, equatorial and longitudinal diameters, firmness, pH, titratable acidity, soluble solids, vitamin C, reductor sugars and total reductor sugars in three ripening stadiums defined by the color of the peel (dark green, light green and yellow green). Among the physical and chemical attributes, only the firmness diminished with the increase of the levels of weekly precipitations for the same ripening stadium and also presented decreases between the ripening stadiums. The physical and chemical attributes, with exception of the pH, decreased with the increase of the weekly precipitations accumulated and in bigger intensities for the biggest ripening stadiums.
Influence of pluviometric precipitations in physical-chemical attributes of fruits of guava tree 'Paluma' in different ripening stadiums
Keywords: Acidity; Psidium guajava; Rainfall; Soluble solids